The EU-Japan free trade agreement in evolving global trade politics. - Yoshimatsu, Hidetaka (Asia Europe Journal, 2020)
The European Union (EU) and Japan began to search for the conclusion of a free trade agreement (FTA) around 2010, and formal negotiations on the EU-Japan FTA (EJFTA) began in April 2013. The negotiations took a longer time than expected, reaching a signature on the agreement in July 2018. This article, by taking into account the character of the EJFTA as a representative mega-FTA, examines how two variables—the influence of interconnected FTA structure and political leaders' responses to anti-multilateralism—influenced the development process of the EJFTA. This article makes two main arguments. First, the presence and substance of other FTAs in which the EU and Japan had been involved brought about both positive and negative effects on the development of the EJFTA. Second, moves towards anti-multilateralism and market disintegration in 2016–17 urged Japanese and European leaders to pursue a swift conclusion of negotiations on the EJFTA.